Unveiling Purchase Intention Corroborate By Digital Marketing Strategy: Study Case Cosmetics Industry - Ida Ayu Iswari Pidada; Ni Nyoman Sri Utari Krisnanda; Ni Made Dhian Rani Yulianthi (Universitas Warmadewa, 2024)
The cosmetics and skincare industry has experienced significant growth in worldwide, and this growth has also impacted Indonesia's cosmetics and skincare industry. When purchasing makeup products, it is crucial to consider factors such as shade selection, ingredients, and other important factors. Social media platforms have become a crucial source of information for people, and they offer the advantage of reaching a large audience. The aim of this research is to investigate the impact of social media marketing and FOMO on purchase intention through electronic word of mouth (E-WOM). The study involved 100 respondents aged between 17 to 25 years, who followed the TikTok account @Luxcrime_id and had searched for information about Luxcrime products. The sampling technique used was purposive sampling, and the study employed quantitative methods with Structural Equation Modeling (SEM-PLS). The research findings indicate that social media marketing, FOMO, and electronic word of mouth have a positive impact on purchase intention. Furthermore, the study discovered that social media marketing has a positive influence on purchase intention through electronic word of mouth.